CLINICAL PROSPECTS OF SCALE-UP FOETAL WHARTONS JELLY DERIVED MULTIPOTENT STROMAL CELLS TO FULFIL THE THERAPEUTIC DEMANDS - JAIANAND KANNAIYAN; BALAJI PAULRAJ (International Journal of Pharma and Bio Sciences, 2015)
Increasing clinical application of multipotent stromal cells has led to the development of large-scale manufactured of MSCs. In this context, the final cellular product should meet the various regulatory criteria, such as safety, integrity, strength, purity and quality that have been ascribed to cell therapy products. In this study, we have optimized large scale expansion of WJ-MSCs for clinical and therapeutic applications. The biologic properties of UC-MSCs, such as plastic adherence, morphology, specific surface antigens, and multipotent differentiation potential, were retained after clinical-large scale expansion. The cells formed a monolayer of homogenous spindle-like cells. Cell size underwent no obvious change, as evidenced by the consistent harvested cell density after clinical-scale expansion. We successfully up-scaled up to P2 to get as many as 5.22x109 cells from a single UC and also observed up to P10 with no significant change in viability, stemness and karyotyping. The growth rate were rate of WJ-MSCs as seen by CFU analysis and PD experiments. A set of typical surface phenotypic characteristics by flow cytometry confirmed that more than 95% of the cells reacted with antibodies against CD73, CD90, and CD105 and less than 1% reacted with CD45, CD34, CD79, and HLA-DR. These cells could be induced to differentiation potential of osteogenic, chondrogenic and adipogenic lineages was proved for their exploitation as a potential therapeutic tool to meet increasing therapeutic demands.